PONDOK PESANTREN ISLAM AL-MUKMIN NGRUKI: STUDI TENTANG FAHAM KEAGAMAAN SALAFI - TM, Fuaduddin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
Ngruki pesantren is one which was founded on the basis of Salafi, i.e. the religious view which strives to purl Islamic teachings originated from Al Qur'an and As-Sunnah based on Salafi tradition and culture. The main theme of Ngruki pesantren is the purification of Islamic teachings as ad-Dien wa Daulah by upholding Islamic Syari'ah in a complete way. As Salafi group, there are a number of their teachings and doctrines which may look contradictory to the mainstream in the community. Salafi teachings and doctrines are being internalized more through hidden curriculum: taklim, tausiah, and the cultural environment of the pesantren. Due to the external factors, their socio-religious behaviors often emerge to the surface, and this is considered by certain people as the form of "Salafi radicalism."